A voltage-transient method for characterizing traps in GaN HEMTs. (February 2019) - Zheng, Xiang; Feng, Shiwei; Gao, Yifu; Zhang, Yamin; Jia, Yunpeng; Pan, Shijie
Abstract: Trapping effects in GaN HEMTs still limit their performance. The current-transient methodology has shown advantages in characterizing traps in the device. However, the voltage drift may cause errors in measurements with high accuracy requirements. In this paper, we present a methodology to characterize traps in GaN HEMTs using the voltage-transient measurements. We demonstrate the advantages of this method in terms of simplicity and effectiveness. In particular, it avoids the said problem due to the optimized measuring circuit. With this method, we have identified the time constants and energy levels of traps in the AlGaN barrier layer and the GaN buffer layer, respectively, in the devices. Their trapping and de-trapping mechanisms were also demonstrated at various temperature measurements. A classic exponential dependence of the degradation rate on the channel current was identified. Highlights: A new method to overcome the problem of voltage changes during the monitoring of current transients to characterize traps in GaN HEMTs. The time constants and energy levels of traps were acquired using this voltage-transient method. An exponential dependence of the degradation rate on the channel current was identified in different samples.